Assistance of Catfish Feed Management in Fish Farmer Groups Tanjung Seteko Village, Indralaya, Ogan Ilir - Mukti, Retno Cahya; Jubaedah, Dade; Amin, Mohamad; Marsi; Yulisman (Unram Journal of Community Service, 2025)
One of the obstacles in catfish farming is the high price of artificial feed or commercial feed. One solution is proper feed management, which can increase fish growth and production. The purpose of this activity is to improve the understanding of catfish farmers about feed management. This activity will be carried out in Tanjung Seteko Village, Indralaya, Ogan Ilir. The implementation method involves counselling, training, and technical assistance, as well as production through the empowerment of active participation by partners. This is achieved by transferring knowledge and technology about catfish feed management, which includes proposing lecturers, students, and partners. The results of this activity show an increase in knowledge about feed management.